Educação de Jovens e Adultos e evasão escolar: entre motivos, influencias e desafios na realidade de uma escola em Parintins (AM) - Azevedo, Geisy Machado de (Brasil, 2024)
School dropout, although widely studied and debated in several studies, is still a phenomenon frequently found in Youth and Adult Education (EJA). Her interest in the subject arose from dialogues, readings and studies during her undergraduate studies, as well as personal contact with people who had given up their studies. The main objective is to understand the reasons that influence school dropout and the challenges for Youth and Adult Education in the reality of an EJA school in Parintins (AM). The Paths The methodological findings were outlined by a qualitative approach, through Field Research in a municipal school in Parintins (AM), whose instrument was the semi-open interview with teachers and students enrolled in EJA who dropped out of school in the 2023 school year, or who rarely attend the classroom. It is crucial to highlight that truancy in EJA cannot be addressed in isolation, but rather as part of a broader set of social, economic and educational issues. The voices of the teachers and pedagogical team highlight the oblivion of the modality in several fields and highlight the necessary sensitive and committed look at the EJA subjects.